Improving Primary Education in the Democratic Republic of the Congo: End-Line Results of a Cluster-Randomized Wait-List Controlled Trial of Learning in a Healing Classroom. Issue 3 (3rd July 2019) - Torrente, Catalina; Aber, John Lawrence; Starkey, Leighann; Johnston, Brian; Shivshanker, Anjuli; Weisenhorn, Nina; Annan, Jeannie; Seidman, Edward; Wolf, Sharon; Tubbs Dolan, Carly
Abstract: We used a cluster-randomized, wait-list controlled trial to examine impacts of a school-based social-emotional learning intervention on Congolese students and teachers. Seventy-six school clusters in two groups (A and B) were randomized to treatment or control. The groups differed in geographic location, accessibility, exposure to violence, and external donor investment. We estimated causal impacts in Group A, tested whether those impacts were replicated in Group B, and conducted sensitivity analyses on the pooled sample. Pooled analyses had higher statistical power and were therefore more likely to represent the true average impacts of the program. Improvements in students' perceptions of school predictability and in addition and subtraction, geometry, and reading performance were specific to Group B. Only the effect on addition and subtraction remained significant in the pooled analysis. Improvements in teachers' sense of accomplishment were found in Group A and remained significant in the pooled analysis. We detected no impacts on other outcomes. School-based interventions embedding social-emotional learning principles into the academic curricula are a promising but not yet proven approach to improving children's outcomes in low-income countries affected by war.